Experimental Study of In-plane Mechanical Properties of Carbon Fibre Woven Composite at Different Strain Rates. Issue 4 (May 2017) - Lu, Jiahai; Zhu, Ping; Ji, Qinghui; Cheng, Zhang
Carbon fibre woven composite has been increasingly employed in engineering applications undergoing complex loading conditions. For effective use of composite material in dynamic applications, it is essential to fully understand the mechanical behaviour of composite at different strain rates. In the present study, both in-plane tensile and compressive experiments loaded at 0 degree axial direction and 45 degree off-axial direction of a TC33 carbon fibre woven composite were investigated over the strain rate range from 0.001 to 1000 s −1 . High strain rate tests were carried out using Split Hopkinson Pressure and Tensile Bar apparatus respectively. The results indicated that the in-plane mechanical properties and failure patterns were strain rate sensitive under both tensile and compressive loadings. The mechanical properties, failure patterns and strain rate effect also showed highly direction dependent and tension/compression asymmetric characteristic within the considered strain rate range. For higher strain rate sensitivity under compression than that under tension, the asymmetry of mechanical properties was less obvious with the increase of strain rate. Finally, two phenomenal models were proposed to quantitatively fit the relationship between strength property and strain rate.